Concept and Science of Administrative Law in the Interwar Period in Lithuania - Deviatnikovaitė, Ieva (Teisė, 2018)
Gian Domenico Romagnosi published the first book about administrative law in 1814. The first administrative case in France was examined by the Tribunal des conflits in 1873. Lawyer Antoni Okolski introduced definition of administrative law in Polish language in 1880. In the interwar period, neither a state nor a higher education institution in Lithuania published at its own expense any administrative law book. However, it was analysed in some scientific articles. Thus, the purpose of this study is to analyse them as it allows to establish the development of administrative law in Lithuania.